A systematic review of STEM education research in the GCC countries: trends, gaps and barriers - Fatma Kayan-Fadlelmula; Abdellatif Sellami; Nada Abdelkader; Salman Umer (SpringerOpen, 2022)
Abstract Abundant research conducted in many countries has underlined the critical role of Science, Technology, Engineering, and Mathematics (STEM) in developing human capital in fields important to a nation's global competiveness and prosperity. In the Gulf Cooperation Council (GCC) States, recent long-term policy plans emphasize the ever-increasing need of transition to a knowledge-based economy and preparing highly qualified nationals with credentials in STEM fields to meet the current and future needs of the labor market. Yet, despite multiple educational reforms and substantial resources, national and international indicators of student performance still demonstrate insignificant improvement in GCC students' achievement in STEM subjects. Demonstrably, the GCC youth still lack interest in STEM careers and represent low enrollment rates in STEM fields. This paper presents the results of a systematic review conducted on STEM education research in GCC countries. The review seeks to contribute to the body of the existing STEM literature, explore the factors influencing student participation in STEM, and identify the gaps in STEM education research in those countries.